Analisa Hasil Pengukuran Tahanan Pentanahan Pada Peralatan di Switchyard Gardu Induk Angke PT. PLN (Persero) UIT – JBB Duri Kosambi - Ibnu Hajar; Dela Romadani (Sutet, 2023)
Substation is part of the electric power system that distributes electrical energy from the generator to the load. It is necessary to ensure safety and security guarantees for the installed equipment and humans at the substation. This research discusses the results of measuring grounding resistance on equipment in the switchyard with quantitative methods based on the results of measuring equipment grounding resistance, step voltage, touch voltage. The quantitative method is based on the quality of the equipment grounding resistance at the Angke Substation switchyard. The value of the equipment grounding resistance at the substation must be able to meet the IEEE Std standard 80 – 2000 that is < 1 ?. The smaller the grounding value obtained, the better of the grounding. Based on the results of this study, the value of the grounding resistance of the Angke Substation is 0,13 V. The value of the touch voltage is 651.55 V for humans weighing 70 kg and 481.4 V for humans weighing 50 kg. With the value of the permissible touch voltage is 626 V. The step voltage value is 2135.2 V for a human weighing 70 kg, and 1577.6 V for a human weighing 50 kg. With a permissible step voltage value of 2216 V.